2018
DOI: 10.1002/ecs2.2476
|View full text |Cite
|
Sign up to set email alerts
|

The interactive effects of predator stress, predation, and the herbicide Roundup

Abstract: As the number of studies examining the effects of contaminants grows, ecologists are becoming increasingly aware that contaminants can interact with natural stressors (e.g., competition and predator cues) in their effects on nontarget animals. In amphibians, predator cues can make contaminants more lethal under laboratory conditions, but the opposite outcome has been observed under more natural conditions with stratified water columns; stratification causes more pesticide to be present near the surface while p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 73 publications
(158 reference statements)
0
7
0
Order By: Relevance
“…Exposure to elevated CORT is associated with tadpoles of R. sylvatica and R. pipiens developing deeper tails (an antipredator morphology; Hossie et al, 2010;Middlemis Maher et al, 2013). At higher, but still environmentally relevant, concentrations of Roundup TM the antipredator morphology of deeper tails is induced in wood frog and leopard frog tadpoles (Relyea, 2012) but not in gray tree frog tadpoles, Hyla versicolor (Relyea 2018). Deeper tails aid in escaping from predators as deeper tails deflect lethal predator attacks toward the tail instead of the body of the tadpole (Van Buskirk et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exposure to elevated CORT is associated with tadpoles of R. sylvatica and R. pipiens developing deeper tails (an antipredator morphology; Hossie et al, 2010;Middlemis Maher et al, 2013). At higher, but still environmentally relevant, concentrations of Roundup TM the antipredator morphology of deeper tails is induced in wood frog and leopard frog tadpoles (Relyea, 2012) but not in gray tree frog tadpoles, Hyla versicolor (Relyea 2018). Deeper tails aid in escaping from predators as deeper tails deflect lethal predator attacks toward the tail instead of the body of the tadpole (Van Buskirk et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The increase in tail depth is additive when tadpoles are exposed to both glyphosate and predator cues (Relyea, 2012). In contrast, glyphosate exposure is not associated with morphological changes similar to predator induced changes for tadpoles of Hyla versicolor (Relyea, 2018). In addition to its morphology-based interactions with predator cues, glyphosate may interact with behaviors involved in antipredator responses, as environmentally relevant levels of glyphosate interfere with chemical cue detection and processing (e.g., Tierney et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…In mesocosms assigned the predator‐cue treatment, the cage contained a larval dragonfly ( Anax junius )—a well‐known predator of larval amphibians. Larval amphibians sense predators through chemical cues given off during predation events and can respond by altering their behavior, physiology, and morphology (Crane et al 2017; Relyea 2018). For example, larval dragonflies release kairomones that trigger a response from the larval amphibians.…”
Section: Methodsmentioning
confidence: 99%
“…Natural stressors include variable temperatures, competition, predation, and parasitism (Holmstrup et al 2010), and these stressors can affect a variety of traits, such as morphology development, survival, and immune function (Relyea and Hoverman 2003; Reeve et al 2013; Walls and Gabor 2019). Competition and predation, specifically, are very common in amphibian breeding habitats and have also been shown to interact with anthropogenic stressors, such as pesticides, to make them more or less lethal to amphibians (Relyea 2018). To understand fully how amphibians are affected by the salinization of their habitats, we need to know whether the effects of salinized environments interact with biotic stressors in ways that are additive, synergistic, or antagonistic.…”
Section: Introductionmentioning
confidence: 99%
“…Nonlethal but detrimental effects of herbicide exposure on amphibian behavior, metabolism, skin bacterial communities, and immunity have also been reported (Krynak et al 2017; McMahon et al 2017; Freitas et al 2019; Moreira et al 2019). Effects of herbicide exposure are often species specific (Berrill et al 1994) or dependent on other environmental factors, such as population density, hydroperiod, presence of predators, or temperature (Boone and James 2003; Rohr et al 2011; Relyea 2018). For example, Rohr et al (2011) found that salamander larvae developed faster when exposed to both atrazine and increased temperatures, suggesting that the rapid development may offset some of the detrimental effects of atrazine exposure.…”
Section: Introductionmentioning
confidence: 99%